FACTORS ASSOCIATED WITH MUSCULOSKELETAL DISORDERS AMONG ONLINE MOTORCYCLE TAXI DRIVERS IN THE GRAB SIMPANG NEGARA (GSN) COMMUNITY, MEDAN AREA DISTRICT - Syahputri, Ratu Julia; Siagian, Masryna; Hulu, Victor Trismanjaya (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Musculoskeletal Disorders (MSDs) are one of the most common occupational health problems experienced by online motorcycle taxi drivers, primarily due to repetitive physical activity, non-ergonomic working positions, and high work pressure. This study aims to analyze the factors associated with the incidence of MSDs among online motorcycle taxi drivers in the Grab Simpang Negara (GSN) Community, Medan Area District. The research used a cross-sectional design with a quantitative approach involving 77 respondents. The instruments used were the Nordic Body Map questionnaire to assess MSDs complaints and the HSE (Health and Safety Executive) questionnaire to evaluate work-related stress levels. Data analysis was conducted using univariate and bivariate methods (Chi-square test), and multivariate analysis using logistic regression. The results showed that 59.7% of respondents experienced symptoms of MSDs. There was a significant relationship between age, length of employment, and work stress level with the incidence of MSDs (p ≤ 0.05), with work stress being the dominant factor. These findings highlight the importance of preventive efforts through improved working conditions and integrated stress management for online motorcycle taxi drivers.